2013
DOI: 10.1371/journal.pone.0072900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reactive Oxygen Species Generation in Rabbit Corneal Epithelial Cells on Inflammatory and Apoptotic Signaling Pathways in the Presence of High Osmotic Pressure

Abstract: It is generally accepted that high osmotic pressure (HOP) of lacrimal fluid is the core mechanism causing ocular inflammation and injury. However, the association between HOP and the regulation of cell inflammatory response and apoptotic pathways remains unclear. In the present study, we used HOP to interfere with in vitro cultured rabbit corneal epithelial cells, and found that HOP increased the generation of reactive oxygen species (ROS) in rabbit corneal epithelial cells, and increased ROS in turn induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…27 As this osmotic challenge elicited NLRP3 inflammasome activation and increased bioactive IL-1b release mediated by increases in caspase-1 expression in this tissue, 7 we determined whether inhibition of TRPM2 activation blunts these downstream responses. First, it was necessary to identify a final noncytotoxic DMSO concentration that solubilized ACA, a liposoluble substance.…”
Section: Trpm-2 Inhibition Suppresses Hyperosmolarinduced Increases Imentioning
confidence: 99%
“…27 As this osmotic challenge elicited NLRP3 inflammasome activation and increased bioactive IL-1b release mediated by increases in caspase-1 expression in this tissue, 7 we determined whether inhibition of TRPM2 activation blunts these downstream responses. First, it was necessary to identify a final noncytotoxic DMSO concentration that solubilized ACA, a liposoluble substance.…”
Section: Trpm-2 Inhibition Suppresses Hyperosmolarinduced Increases Imentioning
confidence: 99%
“…To help understand the pathogenesis of DED, hyperosmolar conditions are often used because they reproduce the environment in contact with the ocular surface in the pathology. These experiments have shown that HO was responsible for ocular surface cell death [ 18 , 19 ], reactive oxygen species formation [ 20 , 21 ], activation of MAPKs such as p38, JNK and ERK [ 22 24 ] and increases in production of matrix metalloproteinases (MMP) [ 22 ], and pro-inflammatory cytokines such as IL-1β, TNF-α, IL-8, IL-6 and CCL2 [ 25 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress caused by overproduced reactive oxygen species (ROS) has been recognized to be an important mechanism involved in ocular surface inflammation and dryeye disease, such as ROS-induced NLRP3 inflammasome activation, JNK pathway, CD95/CD95L apoptotic signaling activation, and so on. [24][25][26][27][28] Reactive oxygen species are generated under normal physiological conditions from the mitochondrial electron transport chain and other sources, and play an important role in activating cellular signaling for survival. However, high levels of ROS cause oxidative stress and cell injury, including at least three reactions, lipid peroxidation of membranes, intracellular oxidative modification of proteins, and oxidative damage to DNA.…”
mentioning
confidence: 99%